УЛЕМИНА ПЕРЦЕПЦИЈА ОСМАНСКИХ ВЕЛИКИХ ВЕЗИРА БОСАНСКОГ ПОРЕКЛА – НА ПРИМЕРУ БАШТЕ ВЕЗИРА, ПРВОГ ОСМАНСКОГ БИОГРАФСКОГ ДЕЛА О ОСМАНСКИМ ВЕЛИКИМ ВЕЗИРИМА (Prilozi za književnost, jezik, istoriju i folklor, 2024)
‘THE ‘ULEMA’S PERCEPTION OF OTTOMAN GRANDVIZIERS OF BOSNIAN ORIGIN – THE EXAMPLE OF THEGARDEN OF VIZIERS, THE FIRST OTTOMANBIOGRAPHICAL WORK ON OTTOMANGRAND VIZIERSThe Ottoman state was a society in which different religions, languages and ethnicities coexisted throughout its whole history. With this regard, cosmopolitism and tolerance in the Ottoman Empire are a topic often spoken of in the literature related to it. In this work, some ethnic-based dissonant tones present within the Ottoman ruling military-administrative class are brought up. The article suggests that there existed ethnic intolerance which members of ‘ulemâ, the Ottoman learned class, as “old Muslims” of Turkish origin, expressed toward grand viziers „new Muslims” and “new Ottomans” because of their Bosnian origin. The pivot of this suggestion is a sentence from The Garden of Viziers written in 1718 in which the author, the Ottoman intellectual and member of ‘ulemâ Osmânzâde Ahmed Tâ’ib, in a disapproving tone emphasises Bosnian origin of the Grand Vizier Salih Pasha, brought to Istanbul through devshirme (child levy) at the beginning of the seventeenth century. This was not a solitary example of ‘ulemâ’s intolerance toward Ottoman statesmen who were converts and of devshirme origin. The work does not, however, absolutely reject cosmopolitism and tolerance in the Ottoman society, but only relativises them and suggests the utmost reserve when it comes to underlining them as common features of the Ottoman society.